Aufarbeitung: Die DDR in der Erinnerungskultur. Begleitband zur gleichnamigen Ausstellung / Coming to Terms with the Communist Past in Germany. Companion volume to the eponymous exhibition - Mählert, Ulrich; Wolle, Stefan (Metropol Verlag, 2023)
“Aufarbeitung. Coming to Terms with the Communist Past in Germany” is a contribution to the history of reunited Germany. The book accompanying the exhibition of the same name sheds light on the efforts since 1989 to reckon with the communist dictatorship and German division. The book presents 110 photos and documents as well as concise texts in German and English. The authors are the historians Ulrich Mählert & Stefan Wolle, who designed the exhibition for the Federal Foundation for the Study of the Communist Dictatorship in Germany. QR codes with links to short film documents give the book a multimedia dimension.